Finding Life in Literacy. (November 2018) - Heath, Shirley Brice
By the second decade of the 21st century, mentally ill youth who committed suicide and sometimes killed others before they killed themselves received considerable attention in the media of the United States. In none of the accounts of these individuals did their literacy lives come up for consideration. This case study details the role of literacy in the life of a young woman who suffered a traumatic brain injury in her teens. As she aged, she tried suicide multiple times, escalating from cries for help to jumping in front of a moving train. Thereafter, she lived in a care facility with half a dozen elderly residents suffering from various neurological and physical disabilities. Following several months of adaptation, she returned to her childhood love of children's books and gradually escalated her reading of national newspapers and adult nonfiction works aloud for other residents. During meals and visits from the grandchildren of residents, she read children's books or poems, and she recorded in her own writings responses to these readings and created short poems. Adaptation to the reality that for the remainder of her life, she would live in such a facility came rapidly and without regression to depression once she found that residents needed and wanted her as their "library, " conversationalist, and inspiration. Four principles of literacy retention and restoration in an individual's life follow from this case.